Bad nature : a novel - Courage, Ariel (Henry Holt and Company, 2025)
"Armed with a terminal diagnosis, a grudge, and a rental car, forty-year-old Hester sets out to fulfill her lifelong dream of killing her father in this brilliantly subversive and bleakly funny novel It's Hester's fortieth birthday when she's diagnosed with terminal cancer, and she knows immediately what she must do: abandon her possessions and drive to California to kill her estranged father. With no friends or family tying her to the life she's built in New York City, she quits her wildly lucrative job in corporate law and sets off. She hasn't made it far when she runs into John, an environmental activist in need of a ride to different superfund sites across the United States. From five-star Midwestern hotels to cultish Southwestern compounds, the two slowly make their way across the country. But will the revelations they make along the way dissuade Hester from her final goal? Ragingly singular and surprisingly moving, Bad Nature is a story of stunning detours and twists until its final destination. Part road trip novel, part revenge tale, part a lament of our ongoing ecological crisis, it's ultimately a deft examination of the indulgence of holding grudges, moral ambivalence, and the eternal possibility of redemption"--